FOREIGN CAPITAL INVESTMENT IN UPSTREAM OIL AND GAS: A CASE STUDY OF PASE WORKING AREA, ACEH PROVINCE, INDONESIA - Nurdin Nurdin; Amira Amira (Universitas Syiah Kuala, 2021)
This paper explores the management of the Pase Upstream Working Area of oil and gas (MIGAS) by Triangle Pase Inc as a Foreign Direct Investment, which is not according to the Revenue Sharing Agreement signed by the parties and regulations Indonesia. The main obstacle in the implementation of Foreign Direct Investment in the Upstream MIGAS sector in Pase Working Area is the failure to establish the APGE as a Joint Venture Company that operated as a subsidiary company required by the Investment Law and Regulation of the Minister of Trade 08/2017. It has a severe impact on the Aceh government's income from the cooperation management of the Upstream MIGAS sector in the Pase Working Area. The Arbitration Award that BANI has granted, which rejected The PDPA lawsuit, has reduced and even eliminated the privilege of the Aceh Government in managing the Upstream MIGAS sector in the Pase Working Area as stipulated by Law Number 11 of 2006 and Aceh's MIGAS Government Regulation. As a solution, the BPMA has ordered Triangle Pase Inc. to revise the legality of APGE to comply with the prevailing laws and regulations in Indonesia. Therefore, the BPMA, as the regulator, and The PDPA as the parties in the Upstream MIGAS management in the Pase Working Area and Commission III of the Aceh's House of Representative to immediately summon Triangle Pase Inc. to resolve the dispute between The PDPA and Triangle Pase Inc. The PDPA, as the losing party in the award granted by BANI, needs to take immediate legal steps to prevent the execution of the BANI's Arbitration AwardKeywords: BPMA; Pase Upstream Working Area; MIGAS; Aceh Province